A Comprehensive View on Drugs-Induced Cardiotoxicity and Its Prevention - Abdulnaser Ali; Musab Khalaf; Abdulla A. Ahmad (University of Mosul, 2024)
Background: The prevention of drug-induced cardiotoxicity is a complicated challenge facing healthcare providers during the last few decades. This challenge is raised from the unclear definition of the term “cardiotoxicity”, the overlapping of the symptoms of heart dysfunction due to the underlying diseases and the used drugs or using a combination of drugs which makes it difficult to distinguish between the side effects of each drug. Objective: This review discusses the most causative agents of cardiotoxicity, and their mechanisms to induce cardiac muscle damage, and finally focuses on the most applicable methods to deal with these dangerous heart problems. Methods: The search method involved electronic databases, including PubMed, Web of Science, Springer, Google Scholar, and others to resume relevant trials of heart disease published in the period between 2010-2023. Conclusion: Cardiotoxicity is a common substantial adverse effect of many drugs including anticancer drugs and others. The prevention methods may include medications, such as (Enalapril or carvedilol), supplementation with antioxidants, or cardioprotective natural products.